Unforeseen sequela of a traditional remedy: A garlic burn case report - Nor Amal Lina Shamsudin; Chee Hon Yee; Yoon Chin Yap (Malaysian Family Physician)
Garlic is one of the most popular natural home remedies for a variety of illnesses. Many different cultures have recognised its beneficial properties as a herbal remedy since ancient times. Nevertheless, inappropriate usage of garlic can cause unwanted side effects despite its numerous positive qualities. Although they may appear to be the least dangerous, natural remedies like garlic can also cause burn themselves. Garlic typically resulted in second-degree burns, but in some cases, necrotic tissue could also develop. This case report described burn injuries caused by the application of raw garlic. We aimed to demonstrate the possible adverse effects of using garlic as a natural home remedy as well as to educate the public and healthcare providers about inappropriate usage of natural home remedy for self-treatment.